Professor dr R.W.B. Stephens. Awarded the gold medal of the American Acoustic Society // The Secon Congress of the Federation of Acoustical Societes of Europe Fase–78 - ZIENIUK, Jerzy K.; CZARNECKI, Stefan; DEPUTAT, Julian (Archives of Acoustics, 1978)
Prof. Raymond W. B. STEPHENS from Great Britain, a friend of Poland and of Polish acousticians, was the first foreigner to receive the highest scientific distinction of the Acoustical Society of America presented every two years for outstanding achievements in the field of acoustics. // The Federation of Acoustical Societies of Europe has decided that the Second FASECongress will be held in Poland. The Congress is to be organized by the Acoustical Committee of the Polish Academy of Sciences and the Polish Acoustical Society in collaboration with the Institute of Fundamental Technological Research (IPPT —PAN).